1996
DOI: 10.1021/jp952289q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Aqueous Nucleobases, Nucleosides, and Nucleotides on Compost-Derived Humic Acid. 2. Naturally Occurring Purines

Abstract: This paper describes adsorption of the aqueous purines adenine (10), adenosine (11), adenosine 5′monophosphate (12), guanosine (13), and guanosine 5′-monophosphate (14) on compost-derived humic acid (HA) over the solute concentration (12-1200 µM) and temperature (10.0-40.0°C) ranges used with pyrimidine solutes in Part 1. Nucleobase 10 and nucleosides 11 and 13 are neutral under the experimental conditions, while nucleotides 12 and 14 are monoanions. All the purines interact with HA, but only adenine causes HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(49 citation statements)
references
References 16 publications
4
45
0
Order By: Relevance
“…Equilibrium Constants. Equilibrium constants K i for uracil adsorption on GHA follow the general trend found with CHA: K C < K B < K A . , Notable is that K A for uracil adsorption on CHA at 25.0 °C is about 13 times larger than with adsorbent GHA (Table ). Otherwise, there is remarkable similarity of K i at 25.0 °C for uracil adsorption on CHA and GHA.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Equilibrium Constants. Equilibrium constants K i for uracil adsorption on GHA follow the general trend found with CHA: K C < K B < K A . , Notable is that K A for uracil adsorption on CHA at 25.0 °C is about 13 times larger than with adsorbent GHA (Table ). Otherwise, there is remarkable similarity of K i at 25.0 °C for uracil adsorption on CHA and GHA.…”
Section: Resultsmentioning
confidence: 54%
“…Like uracil, uridine is a neutral molecule in the pH range 4.6−5.1 used for the measurements, while uridine-5‘-monophosphate is a monoanion 30 in the pH range 3.4−4.6 used to measure its isotherms. These differences check the effects of solute charge and molar mass on the adsorption parameters. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marschner & Bredow () and Khairy et al . (,b) have both observed that a rise in temperature moves the system toward a higher share of non‐sorbed reactants, and temperature has a progressively larger effect as more energy is needed to desorb reaction partners. Temperature also increases diffusion and dissolution, both of which increase substrate availability to soil microbes and leaching losses of soil carbon (Xu & Saiers, ).…”
Section: A Way Forward Through a New Conceptual Frameworkmentioning
confidence: 99%
“…2(c) likely reflects the macroscopic framework of the original aqueous gel and those of waterlogged HAs in soils and sediments. 23 for adsorption of 14 nucleic acid constituents (NACs) on a solid compost-derived HA and on solid HA particles from different soil sources without or with added Hg II 24 show that HAs can be purified to the point where they become understandable. The data fit the Langmuir model for reversible solute adsorption in sequential steps labelled i = A, B and C. 14,[22][23][24] Analysis gives the stoichiometric site capacity ν i and the equilibrium constant K i for each solute and step.…”
mentioning
confidence: 99%